Post-pastoral and the Nonmodern: Jean Giono’s Engagement with Nature - Gina Stamm (Studies in 20th & 21st Century Literature, 2018)
Dismissal of the pastoral as naïve and hostile to progress echoes the critiques which Bruno Latour, in We Have Never Been Modern, makes of what he calls the “antimodern” sensibility. Rather than advocating for an abandonment of the past, however, Latour puts forth a position he calls “nonmodern,” one that allows for recognition of the value of the past and of the natural without idolizing it, that does not demand the forward motion of the modern impulse. While eschewing the “modern” label, he seeks a way to resolve contemporary dichotomies of man vs. nature, human vs. technological, etc., which find themselves entangled in issues such as pollution, climate change, and the political response to these issues. Like the antimodern, the pastoral, according to Terry Gifford, traditionally involves a movement of return (to the land, the past, etc.). This movement itself has also been viewed as suspiciously tied to fascist “back to the land” nostalgia. This same accusation has been leveled at Jean Giono, whom Catherine Savage Brosman suggests “Perhaps…comes closest in our century to being a true pastoral writer” (220). His depictions of the rural environment, however, are not blindly nostalgic for the bucolic, despite the intense beauty of rural landscapes, the sensual pleasure he often derives from them, and his suspicion of city life and industrialization. Giono's writing shows a profound ambivalence towards nature, with which he nonetheless sees humanity as being inextricably intertwined. This view of the destruction possible in nature, combined with the recognition of humanity’s engagement in the natural world, situates Giono in what Terry Gifford would call the post-pastoral, while also demonstrating an attitude towards time and progress that allows us to see post-pastoral writing as a literature appropriate to the nonmodern approach advocated by Latour.
Keywords: Jean Giono; pastoral; Bruno Latour; nonmodern; ecocriticism; politics